A potent bioactive fraction against colon cancer from Plectranthus vettiveroides - Faisal M. Athikkavil; Sreekumar U. Aiswarya; Remya Johny; Meghna Sudhesh; Amrutha A. Nisthul; Ravi S. Lankalapalli; Ruby J. Anto; Smitha V. Bava (Open Exploration Publishing Inc., 2023)
Aim: This study was designed to investigate the anticancer efficacy of the organic leaf extracts of the plant, Plectranthus vettiveroides (P. vettiveroides), and to analyze the molecular mechanism of the anticancer activity. Methods: The leaf extracts were prepared by polarity-graded serial extraction of the dried leaf powder. The cytotoxic effect of the extracts was analyzed by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The most active ethyl acetate extract was subjected to bioactivity-guided fractionation by column chromatography, which yielded a cytotoxic fraction designated as the P. vettiveroides fraction (PVF). The anticancer property of PVF was confirmed further by clonogenic assay. The mechanism of PVF-induced cell death was analyzed by flow cytometry and fluorescence microscopy. Additionally, the effects of PVF on apoptotic and cell survival pathways were analyzed using western immunoblot analysis. Results: A bioactive fraction PVF, was isolated from the ethyl acetate leaf extract. PVF showed significant anticancer activity against colon cancer cells, whilst normal cells were comparatively less affected. PVF induced strong apoptotic stimuli in colorectal carcinoma cell line HCT116, involving both extrinsic and intrinsic pathways. Investigation into the molecular mechanism of anticancer activity of PVF in HCT116 cells revealed that the fraction activates the pro-apoptotic pathway via tumor suppressor protein 53 (p53) and inhibits the anti-apoptotic pathway by regulating phosphatidylinositol 3-kinase (PI3K) signaling. Conclusions: The findings of this study demonstrate, with mechanism-based evidence, the chemotherapeutic potential of a bioactive fraction PVF, derived from the leaves of the medicinal plant P. vettiveroides against colon cancer.